HUBUNGAN PENDIDIKAN IBU DAN ASI EKSKLUSIF DENGAN KEJADIAN STUNTING DI DESA TB WILAYAH KERJA PUSKESMAS CIBADAK TAHUN 2019 - Rita Ariesta; Neneng Rahmawati (Jurnal Obstretika Scientia, 2020)
According to data obtained from the Lebak District Health Office in 2018, the highest stunting incidence occurred in Mount Kencana at 492, the second highest incidence occurred in Pamandegan sub-district at 156 and the third highest stunting incidence occurred in Cipanas at 132 based on these data with the location The area that is the easiest to reach is TB Village and the researchers conducted research in the work area of the Cibadak Health Center. The purpose of this study was to find out whether there was 2019. The study used a 1:1 case control analytic design with the relationship between maternal education and exclusive breastfeeding with the incidence of stunting in children aged 6-12 years "In TB Village In the work area of the Cibadak Public Health Center in 2019. approach. Analytical sampling using purposive sampling obtained 44 respondents, namely 22 case data groups and 22 control groups. Univariate analysis data showed that almost half of the children were stunted. (50.0%) of all respondents, almost all of them still found mothers with low education (79.5%), and most of the children were not given exclusive breastfeeding (56.8%) from bivariate analysis data, it shows that respondents with low education are almost entirely (81.8%) experiencing stunting compared to those who are not stunted (77.3%) there is no relationship between education and stunting in TB village in 2019 (α = 0.05 p value p = 0.709 where the value (p 0.05) but there is a relationship between exclusive breastfeeding and stunting in children in Tambak baya village with a value of = 0.05 p value p = 0.00 where the value (p0.05) The importance of preventing stunting by increasing parents' knowledge about how to exclusively breastfeed from birth and continue breastfeeding for up to 2 years